2017
DOI: 10.1159/000470832
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Thermography in Surgery of Newly Diagnosed Glioblastoma Multiforme: A Technical Case Report

Abstract: Infrared thermography (IRT) is a real-time non-contact diagnostic tool with a broad potential for neurosurgical applications. Here we describe the intraoperative use of this technique in a single patient with newly diagnosed glioblastoma multiforme (GBM). An 86-year-old female was admitted in the clinic with a 2-month history of slowly progressing left-sided paresis. Neuroimaging studies demonstrated an irregular space-occupying process consistent with a malignant glioma in the right fronto-temporo-insular reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…IrT has been used to detect lower or higher physiological activity. [9,10] It measures the electromagnetic radiation emitted by the objects and creates a thermal map with different colorpatterns, according to the recording. [15] is technology was first used for military applications in the 1960s and since then, it has been used for medical applications in different animal species and for several purposes, [10] being one of its first medical applications in the detection of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…IrT has been used to detect lower or higher physiological activity. [9,10] It measures the electromagnetic radiation emitted by the objects and creates a thermal map with different colorpatterns, according to the recording. [15] is technology was first used for military applications in the 1960s and since then, it has been used for medical applications in different animal species and for several purposes, [10] being one of its first medical applications in the detection of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[7,14] Neoplasms and normal tissue produce and transfer heat in a different manner due to a decreased metabolic rate of the tissues surrounding and superimposed by the perilesional edema and low tumor microvessel density due to concomitant ischemia. [10] Glial tumors are hypothermic and brain metastases are hyperthermic in comparison with healthy brain tissue, and infrared thermography mapping (ITM) can improve the accuracy of their resection. [3] ITM in neurosurgery has been used with good results to monitor cerebral blood flow after the resection of an arteriovenous malformation, to observe patency of bypass and to prevent irreversible damage due to ischemia during surgery, in temporary occlusion of brain arteries, among other scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…[3] ITM in neurosurgery has been used with good results to monitor cerebral blood flow after the resection of an arteriovenous malformation, to observe patency of bypass and to prevent irreversible damage due to ischemia during surgery, in temporary occlusion of brain arteries, among other scenarios. [1,5,7,9,10,14,16] Intraoperative IT is becoming a promising new real-time diagnostic method because it is non-invasive, radiation free, avoids exposing the patient to drugs or contrast media and it has no known side effects.…”
Section: Introductionmentioning
confidence: 99%
“…The two main factors that can contribute to hypothermia in the surface region of the brain corresponding to the epicenter of a tumor are (a) decreased metabolic rate of the tissues surrounding and superimposed by the perilesional edema and (b) low tumor microvessel density due to concomitant ischemia. [ 6 ] It has been shown that glial tumors are hypothermic and brain metastases are hyperthermic in comparison with healthy brain tissue. [ 2 ] Other studies have used IT in neurosurgery to monitor cerebral blood flow after resection of an arteriovenous malformation, observation of patency of bypass, temporary occlusion of arteries of the brain, among others.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 10 ] Intraoperative IT is becoming a promising new real-time diagnostic method: noninvasive, radiation-free, without exposure to drugs and without any known side effect. It can also improve the accuracy of tumor resections, as well as the assessment of cerebral blood flow in vascular neurosurgery, to prevent the irreversible damage due to ischemia during surgery,[ 3 6 ] among other potential indications.…”
Section: Introductionmentioning
confidence: 99%